O jeszcze jednej metodzie prognozowania ryzyka operacyjnego w przedsiębiorstwie - Witkowski, Marek (About Another Method of the Operating Risk Estimation in an Enterprise, 2006)
Operating risk is one of the basic risks occurring in an enterprise. It can be measured by using different indicators. One of them is described by the relation of fix costs to global costs. In this presentation we suggest using this indicator to calculate creep-regression model of costs what allows us to use this model to create an operating risk prognosis. The Results of this empirical survey lead to assumption that this model has many practical and scientific values, because:- operating risk- indicators are not hampered by errors connected with a small amount of observations,- this method gives a chance to get to know "the history" of managing the company,- operating risk-indicators have a clear interpretation,- this method results in operating risk- prognosis whose precision can be objectively evaluated (even though this is possible only in an indirect way),- this method is very useful in creating short-term prognosis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 328-335